Polygynous Marriages among the Kyrgyz : Institutional Change and Endurance - Cariou, Len; Guggenheim, Charles (Book collections on Project MUSE., 1989)
The Johnstown flood of 1889 was one of the most devastating disasters in America's history. Through real and recreated scenes, this film retells the story.